(untitled) (JED (Jurnal Etika Demokrasi), 2025)
The urgency of this study arises from the limited empirical evidence on how technology-based Pancasila education can strengthen students’ learning motivation and digital literacy in vocational school settings, whereas most technology integration studies have focused on science and vocational subjects. This study aims to analyze the influence of technology-based Pancasila learning on students’ learning motivation and digital literacy in state vocational schools in Jeneponto Regency. A quantitative descriptive–correlational design was employed involving 97 students selected through purposive sampling; data were collected using validated questionnaires and analyzed using simple linear regression. The findings indicate that technology-based Pancasila learning has a positive and statistically significant effect on learning motivation (B = 0.702; p < 0.001), explaining 70.7% of its variance, and on digital literacy (B = 0.766; p < 0.001), explaining 69.7% of its variance. These results suggest that systematic integration of digital platforms and media in Pancasila instruction is effective in promoting both affective engagement and critical use of digital information among vocational students. The novelty of this research lies in providing contextual empirical evidence that technology-enhanced learning is not only relevant for STEM and vocational content, but also highly effective in the domain of Pancasila education to foster 21st-century competencies. This study contributes theoretically by expanding the discourse on technology-based civic and character education and, practically, by offering pedagogical implications for optimizing technology integration in Pancasila learning in vocational schools.